2014
DOI: 10.1371/journal.pone.0103492
|View full text |Cite
|
Sign up to set email alerts
|

Resting States Are Resting Traits – An fMRI Study of Sex Differences and Menstrual Cycle Effects in Resting State Cognitive Control Networks

Abstract: To what degree resting state fMRI is stable or susceptible to internal mind states of the individual is currently an issue of debate. To address this issue, the present study focuses on sex differences and investigates whether resting state fMRI is stable in men and women or changes within relative short-term periods (i.e., across the menstrual cycle). Due to the fact that we recently reported menstrual cycle effects on cognitive control based on data collected during the same sessions, the current study is pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
109
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(121 citation statements)
references
References 93 publications
10
109
1
Order By: Relevance
“…Fourth, while we did not control for parity, menopausal stage, endogenous hormone cycling (menstrual cycle) or exogenous hormone administration (e.g., oral contraceptive pills). Some (Petersen et al 2014), but not all studies (Hjelmervik et al 2014), demonstrate the effects of sex steroid hormones on brain connectivity. However, there was only a small proportion of women in the present study on oral contraceptives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, while we did not control for parity, menopausal stage, endogenous hormone cycling (menstrual cycle) or exogenous hormone administration (e.g., oral contraceptive pills). Some (Petersen et al 2014), but not all studies (Hjelmervik et al 2014), demonstrate the effects of sex steroid hormones on brain connectivity. However, there was only a small proportion of women in the present study on oral contraceptives.…”
Section: Discussionmentioning
confidence: 99%
“…OT and AVP may have sex-dependent associations with cognitive and emotional brain networks, particularly in ones showing sex differences (Hjelmervik et al 2014; Sacher et al 2013). To our knowledge, no study has examined associations between these peripheral hormones and functional brain connectivity.…”
Section: Introductionmentioning
confidence: 99%
“…We additionally used a network with whole-brain coverage consisting of 264 nodes (we here refer to it as Connectome ; Power et al 2011) to predict the five personality traits to test if personality can be better predicted by specific functional networks or a rather unspecific whole-brain network. In addition, in light of the previous findings of sexual dimorphism in the relationships between brain structure and personality traits (Nostro et al 2016) as well as gender differences in RSFC (Allen et al 2011; Filippi et al 2013; Hjelmervik et al 2014; Weis et al 2017) and personality (Yang et al 2015), these analyses were performed in a gender-mixed sample as well as separately in male and female subsamples.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a functional connectivity (FC) method is used to describe the relationships between the neuronal activation patterns of anatomically distinct brain regions, revealing the level of functional communication between them . Two recent studies of resting state connectivity in females have demonstrated that the FC method shows sensitivity to investigate resting state connectivity data across the menstrual cycle . Thus, combining fALFF and FC may provide new insight into the complex role of the HIPP in the neural mechanisms of PMS.…”
mentioning
confidence: 99%